PERAN MEDIA SOSIAL DALAM KEGIATAN PEMBELAJARAN DARING - Wijaya, Celine Mevia; Emanuelawati, Ester; Pratiwi, Intan Oktavia Ajeng (2021)
Learningactivitieshavechangedaccordingtothecurrentpandemicconditionsnamelyonlinelearning.Whereonlinelearningisfocusedontheuseoftechnologyitcannotbedeniedthattechnologyisdevelopingveryrapidlyandsignificantly.Oneexampleoftechnologicaldevelopmentsistheaspectofsocialmedia.Almosteveryoneusessocialmediaintheirdailylife.Themethodusedinthisresearchisthecasestudymethod.Eitherusedtocommunicatewithotherindividualsorforlearningmedia.Giventhatmanystudentsfeelboredinonlinelearningactivitiesbecausetheyfeeltheyhavenotmaximizedexistingtechnology.Thereforeitishopedthatsocialmediacanbeanotheralternativeinonlinelearningactivitiesconsideringthecurrentlifestyleofmillennialchildren.KataKunciPembelajarandaringTeknologiMediasosialAnakmilenial